Karakteristik Kepemimpinan Inovatif dalam Mengoptimalkan Mutu Pendidikan - Fitrah, Putri Fauziatul; Hairunnisa, Hairunnisa; Ayuningtyas, Indah; Anantia, Tasya Dewi (ALSYS, 2021)
This research is motivated by the discovery of a lack of innovative leadership in education. In this research, the writer will formulate the characteristics of innovative leadership in education. This writing uses a qualitative method through a library research approach. This research is descriptive and analyzes information. Data collection was carried out by group discussion by finding scientific studies and information from various sources. The results of this study indicate that the characteristics of innovative leadership in education are said to be successful if the leader innovates to be able to develop all potential resources that will make changes to improve the quality of education in improving processes and products that are more effective, efficient and relevant.